Equação Exponencial!
Resolvam:
evenilsonwonderwall:
Moleza. rs
Soluções para a tarefa
Respondido por
3
Tranformando tudo em base 3, temos:
![3^{-2x^2 + 2} . 3^{3-3x} = 3^{2x + 7} 3^{-2x^2 + 2} . 3^{3-3x} = 3^{2x + 7}](https://tex.z-dn.net/?f=+3%5E%7B-2x%5E2+%2B+2%7D+.+3%5E%7B3-3x%7D+%3D+3%5E%7B2x+%2B+7%7D+)
![3^{-2x^2 -3x + 5} = 3^{2x + 7} 3^{-2x^2 -3x + 5} = 3^{2x + 7}](https://tex.z-dn.net/?f=+3%5E%7B-2x%5E2+-3x+%2B+5%7D+%3D+3%5E%7B2x+%2B+7%7D+)
Faz a equação de 2º grau...
-2x² - 3x + 5 = 2x + 7
-2x² - 5x - 2 = 0
Chega-se nas raizes -1/2 e -2 através de bhaskara....
Faz a equação de 2º grau...
-2x² - 3x + 5 = 2x + 7
-2x² - 5x - 2 = 0
Chega-se nas raizes -1/2 e -2 através de bhaskara....
Perguntas interessantes
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Matemática,
1 ano atrás